Production process and application of modified polyvinyl alcohol flame-retardant adhesive

Through the production process of modified polyvinyl alcohol flame retardant adhesives, additives such as modified boron nitride and guanidine phosphate are mixed with polyvinyl alcohol to form adhesives with high flame retardant properties, which solves the problem that existing flame retardant adhesives cannot effectively prevent internal combustion of wood materials, and achieves the efficient fire-retardant performance of flame retardant solid wood composite floors.

CN119709053APending Publication Date: 2025-03-28DAYA JIANGSU FLOOR
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411936746.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Existing flame retardant adhesives have limitations in improving the fire resistance of wood materials, especially flame retardant paint can only perform flame retardant on the surface and cannot effectively prevent combustion inside the wood materials.

Method used

The production process of modified polyvinyl alcohol flame retardant adhesive is adopted, and modified boron nitride is formed by mixing polyvinylpyridone with boron nitride and ultrasonic dispersing in ethanol, followed by adding ammonia water and ethyl orthosilicate and stirring. Then the modified boron nitride is mixed with guanidine phosphate and polyvinyl alcohol, and after heating and stirring, it forms a colloidal form, and the pH value is adjusted by an acid neutralizer. Finally, ethylene glycol, methylcellulose, zinc chloride and boric acid are added to form a modified polyvinyl alcohol flame retardant adhesive.

Benefits of technology

The flame retardant adhesive improves the density of the carbon layer through the layered structure of boron nitride and the cover of silica; the non-combustible gas decomposed by guanidine phosphate during combustion reduces the oxygen concentration and takes away heat, slowing down combustion. The obtained flame-retardant solid wood composite floor has a flame retardant performance of B1 (B) and the smoke release is small.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of adhesives, and relates to a production process of a modified polyvinyl alcohol flame-retardant adhesive, which comprises the following steps: carrying out alkaline hydrolysis by using tetraethoxysilane, covering the surface of boron nitride with SiO2, adding modified boron nitride and guanidine phosphate into a polyvinyl alcohol aqueous solution, heating to form colloid, dissolving again, adjusting the pH value of the system to 5.0-7.0, and cooling to room temperature to obtain the modified polyvinyl alcohol flame-retardant adhesive. And adding 1-5 parts of ethylene glycol, 1-5 parts of methyl cellulose, 0.01-0.1 part of zinc chloride and 0.01-0.1 part of boric acid, and stirring to fully mix, so as to obtain the water-based paint. The flame-retardant solid wood composite floor is also applied to wood product processing, such as floors and furniture, in particular to preparation of flame-retardant solid wood composite floors. According to the flame-retardant floor, the surface of the floor is coated with the flame-retardant paint besides gluing, during combustion, the compactness of a carbon layer can be improved through the unique layered structure of boron nitride and silicon dioxide in the flame-retardant adhesive, non-combustible gas decomposed in the combustion process can reduce the oxygen concentration around a base body, heat can be taken away, combustion is retarded, and the flame-retardant performance reaches the standard.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adhesives, relates to flame retardant adhesives, and in particular to a production process and application of a modified polyvinyl alcohol flame retardant adhesive. Background Art

[0002] With the continuous strengthening of fire awareness, the fire protection requirements for furniture and floors are also getting higher and higher. There are two main existing flame retardant methods: one is to use adhesives to achieve the flame retardant effect, commonly used are lignin, inorganic high molecular polymers, sodium silicate, etc.; the other is to use flame retardant paint for flame retardancy. Obviously, flame retardant paint can only be used for surface flame retardancy. Once the surface is broken, the wood material inside cannot be flame retardant.

[0003] The invention patent with publication number CN116038849A discloses a formaldehyde-free flame-retardant solid wood composite floor and a modified lignin-based flame-retardant adhesive. The flame-retardant adhesive provided is composed of 20 to 30 parts by weight of ethanol lignin, 20 to 30 parts by weight of hydroxide, 10 to 20 parts by weight of phytate, 30 to 60 parts by weight of a cross-linking agent, 30 to 50 parts by weight of high-temperature soybean meal powder, and 0.1 to 0.2 parts by weight of a tackifier to improve fire resistance.

[0004] The invention with publication number CN117926993A provides a flame-retardant laminated solid wood composite floor and a preparation method thereof, specifically a flame-retardant laminated solid wood composite floor and a preparation method thereof; the scheme first utilizes dopamine hydrochloride and acryloyl chloride to react to generate dopamine monomer, utilizes the double bond of the dopamine monomer to react with a phosphate monomer containing a mercapto group, thereby introducing a catechol group on the side chain of the phosphate monomer to obtain a flame-retardant monomer containing a double bond, and then obtains a light-cured coating by mixing pentaerythritol tetrakis (3-mercaptopropionate), pentaerythritol triacrylate, perfluorodecanethiol and a flame-retardant monomer containing a double bond. The coating is coated on the surface of a wood veneer and then light-cured, which can effectively improve the flame retardant properties of the wood veneer. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a production process of a modified polyvinyl alcohol flame retardant adhesive.

[0006] Technical Solution

[0007] A production process of a modified polyvinyl alcohol flame retardant adhesive, wherein each material involved in the reaction is in parts by weight, comprises the following steps:

[0008] 1) After mixing 5-6 parts of polyvinyl pyridone and 30-35 parts of boron nitride, add 120 parts of ethanol, disperse by ultrasonication to make the mixture uniformly dispersed, and continue stirring;

[0009] 2) adding 10 to 12 parts of ammonia water and 5 to 8 parts of tetraethyl orthosilicate, continuing stirring for 8 to 16 hours, preferably after 12 hours, stopping stirring, standing and centrifuging, washing with ethanol several times, and drying at 60° C. for 24 hours to obtain modified boron nitride;

[0010] 3) Weigh appropriate amounts of polyvinyl alcohol and soft water, heat to 90-95° C., stir for 30-40 minutes to completely dissolve the polyvinyl alcohol, and prepare a polyvinyl alcohol aqueous solution with a concentration of 8-12 wt.%, preferably 10 wt.%;

[0011] 4) adding 3 to 5 parts of modified boron nitride and 8 to 10 parts of guanidine phosphate to 100 parts of polyvinyl alcohol aqueous solution, stirring to obtain a mixed solution, and heating at 60 to 90° C. for 3 to 5 hours until the solution becomes colloidal;

[0012] 5) raising the temperature to 70-95° C., preferably 80° C., and stirring, dissolving the colloidal mixture in 85-115 parts, preferably 100 parts, of water, adding an acidic neutralizer, adjusting the pH value of the system to 5.0-7.0, and cooling naturally to room temperature;

[0013] 6) Add 1 to 5 parts of ethylene glycol, 1 to 5 parts of methyl cellulose, 0.01 to 0.1 parts of zinc chloride, and 0.01 to 0.1 parts of boric acid, and stir to fully mix to obtain a modified polyvinyl alcohol flame retardant adhesive.

[0014] The modified boron nitride prepared by the present invention is a boron nitride surface covered with silicon dioxide. The unique layered structure of the boron nitride and the silicon dioxide can improve the compactness of the carbon layer, thereby effectively improving the flame retardant effect of the polyvinyl alcohol flame retardant; the non-combustible gas decomposed by guanidine phosphate during the combustion process can not only reduce the oxygen concentration around the substrate, but also take away heat; guanidine phosphate can also release highly active phosphorus-containing free radicals to slow down combustion.

[0015] In a preferred embodiment of the present invention, the acidic neutralizer in step 5) is any one of sodium hydroxide and potassium hydroxide. When the hydroxide is burned, the water vapor released by thermal decomposition reduces the combustion temperature and dilutes the oxygen in the air, thereby slowing down the combustion process.

[0016] Methyl cellulose is a thickener, and zinc chloride, boric acid, etc. are functional additives.

[0017] Another object of the present invention is to disclose the application of the prepared modified polyvinyl alcohol flame retardant adhesive, that is, to apply it to the processing of wood products, such as floors, furniture, etc., especially the preparation of flame retardant solid wood composite floors.

[0018] Specifically, a method for preparing a flame-retardant solid wood composite floor comprises the steps of coating the modified polyvinyl alcohol flame-retardant adhesive on the surface of the surface board and the back board, assembling the surface board, the core layer and the back board in a criss-cross manner, cold pressing, hot pressing, curing, slicing, sanding, grooving, coating with flame-retardant paint, and grading and packaging after drying.

[0019] Furthermore, the coating amount of the modified polyvinyl alcohol flame retardant adhesive on the surface panel is 150-180g / ㎡.

[0020] Furthermore, the coating amount of the modified polyvinyl alcohol flame retardant adhesive on the back panel is 160-190 g / m2.

[0021] Furthermore, the cold pressing time is 20 minutes and the pressure is 10-11 kg / cm 2 ;

[0022] Furthermore, the hot pressing time is 360s and the temperature is 93-98°C.

[0023] Beneficial Effects

[0024] The present invention adopts modified silicon nitride and guanidine phosphate and other additives mixed with polyvinyl alcohol to form a flame retardant adhesive, and also coats the floor surface with flame retardant paint. When the floor burns, the unique layered structure of boron nitride and silicon dioxide in the flame retardant adhesive can improve the density of the carbon layer, and the non-combustible gas decomposed during the combustion process can not only reduce the oxygen concentration around the substrate, but also take away heat and slow down the combustion. The flame retardant solid wood composite floor obtained by the present invention has a flame retardant performance that can reach B1 (B) level and a small amount of smoke release. DETAILED DESCRIPTION

[0025] The present invention is described in detail below in conjunction with the embodiments so that those skilled in the art can better understand the present invention, but the present invention is not limited to the following embodiments.

[0026] Example 1

[0027] A production process of a modified polyvinyl alcohol flame retardant adhesive, wherein each material involved in the reaction is in parts by weight, comprises the following steps:

[0028] 1) After mixing 5 parts of polyvinyl pyridone and 30 parts of boron nitride, add 120 parts of ethanol, disperse by ultrasonication to make them dispersed evenly, and continue stirring;

[0029] 2) Add 10 parts of ammonia water and 5 parts of tetraethyl orthosilicate, continue stirring for 8, stop stirring, let stand, centrifuge, wash with ethanol several times, and dry at 60°C for 24h to obtain modified boron nitride;

[0030] 3) Weigh appropriate amounts of polyvinyl alcohol and soft water, heat to 90° C., and stir for 30 to 40 minutes to completely dissolve the polyvinyl alcohol to prepare a polyvinyl alcohol aqueous solution with a concentration of 8 wt.%;

[0031] 4) adding 3 parts of modified boron nitride and 8 parts of guanidine phosphate to 100 parts of 8 wt.% aqueous solution of polyvinyl alcohol, stirring evenly to obtain a mixed solution, and heating at 60° C. for 5 h until the solution becomes colloidal;

[0032] 5) Raise the temperature to 70°C and stir, dissolve the colloidal mixture in 85 parts of water, add sodium hydroxide, adjust the pH value of the system to 5.0, and cool naturally to room temperature;

[0033] 6) Add 1 part of ethylene glycol, 1 part of methyl cellulose, 0.01 part of zinc chloride, and 0.01 part of boric acid, stir to fully mix, and obtain a modified polyvinyl alcohol flame retardant adhesive.

[0034] Example 2

[0035] A production process of a modified polyvinyl alcohol flame retardant adhesive, wherein each material involved in the reaction is in parts by weight, comprises the following steps:

[0036] 1) After mixing 6 parts of polyvinyl pyridone and 35 parts of boron nitride, add 120 parts of ethanol, disperse by ultrasonication to make them dispersed evenly, and continue stirring;

[0037] 2) Add 12 parts of ammonia water and 8 parts of tetraethyl orthosilicate, continue stirring for 12 hours, stop stirring, let stand, centrifuge, wash with ethanol several times, and dry at 60°C for 24 hours to obtain modified boron nitride;

[0038] 3) Weigh appropriate amounts of polyvinyl alcohol and soft water, heat to 95° C., and stir for 30 minutes to completely dissolve the polyvinyl alcohol to prepare a polyvinyl alcohol aqueous solution with a concentration of 10 wt.%;

[0039] 4) adding 5 parts of modified boron nitride and 10 parts of guanidine phosphate to 100 parts of polyvinyl alcohol aqueous solution, stirring evenly to obtain a mixed solution, and heating at 90° C. for 3 h until it becomes colloidal;

[0040] 5) Raise the temperature to 80°C and stir, dissolve the colloidal mixture in 100 parts of water, add sodium hydroxide, adjust the pH value of the system to 7.0, and cool naturally to room temperature;

[0041] 6) Add 5 parts of ethylene glycol, 5 parts of methyl cellulose, 0.1 parts of zinc chloride, and 0.1 parts of boric acid, stir to fully mix, and obtain a modified polyvinyl alcohol flame retardant adhesive.

[0042] Example 3

[0043] A production process of a modified polyvinyl alcohol flame retardant adhesive, wherein each material involved in the reaction is in parts by weight, comprises the following steps:

[0044] 1) After mixing 5 parts of polyvinyl pyridone and 35 parts of boron nitride, add 120 parts of ethanol, disperse by ultrasonication to make them dispersed evenly, and continue stirring;

[0045] 2) adding 11 parts of ammonia water and 6 parts of tetraethyl orthosilicate, continuing stirring for 12 hours, stopping stirring, standing, centrifuging, washing with ethanol several times, and drying at 60° C. for 24 hours to obtain modified boron nitride;

[0046] 3) Weigh appropriate amounts of polyvinyl alcohol and soft water, heat to 93° C., and stir for 40 minutes to completely dissolve the polyvinyl alcohol to prepare a polyvinyl alcohol aqueous solution with a concentration of 10 wt.%;

[0047] 4) adding 5 parts of modified boron nitride and 8 parts of guanidine phosphate to 100 parts of a 10 wt.% aqueous solution of polyvinyl alcohol, stirring evenly to obtain a mixed solution, and heating at 80° C. for 4 h until the solution becomes colloidal;

[0048] 5) Raise the temperature to 80°C and stir, dissolve the colloidal mixture in 100 parts of water, add potassium hydroxide, adjust the pH value of the system to 7.0, and cool naturally to room temperature;

[0049] 6) Add 3 parts of ethylene glycol, 3 parts of methyl cellulose, 0.08 parts of zinc chloride, and 0.08 parts of boric acid, stir to fully mix, and obtain a modified polyvinyl alcohol flame retardant adhesive.

[0050] The preparation process parameters of flame retardant solid wood composite floor are as follows: the coating amount of modified polyvinyl alcohol flame retardant adhesive is 160g / ㎡ for the surface board and 170g / ㎡ for the back board. The surface, core and back of the solid wood composite floor are assembled in a crisscross pattern. The cold pressing time is 20min and the pressure is 10kg / cm 2 ; Hot pressing time 360s, temperature 95℃; curing, slicing, sanding, grooving, coating with flame retardant paint, and drying.

[0051] The modified polyvinyl alcohol flame retardant adhesive prepared in Examples 1-3 was applied to the preparation of flame retardant solid wood flooring. The flame retardant properties of the prepared floors all reached B1 (B) grade after a combustion test.

[0052] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the specification of the present invention, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A production process of a modified polyvinyl alcohol flame retardant adhesive, wherein each material involved in the reaction is in parts by weight, characterized in that: The steps include: 1) After mixing 5-6 parts of polyvinyl pyridone and 30-35 parts of boron nitride, add 120 parts of ethanol, disperse by ultrasonication to make it evenly dispersed, and continue stirring; 2) Add 10-12 parts of ammonia water and 5-8 parts of tetraethyl orthosilicate, continue stirring for 8-16 hours, stop stirring, let stand, centrifuge, wash with ethanol several times, and dry at 60°C for 24 hours to obtain modified boron nitride; 3) Weigh appropriate amounts of polyvinyl alcohol and soft water, heat to 90-95°C, stir for 30-40 minutes to completely dissolve the polyvinyl alcohol, and prepare a polyvinyl alcohol aqueous solution with a concentration of 8-12wt.%; 4) Add 3-5 parts of modified boron nitride and 8-10 parts of guanidine phosphate to 100 parts of polyvinyl alcohol aqueous solution, stir evenly to obtain a mixed solution, and heat at 60-90° C. for 3-5 hours until it becomes colloidal; 5) Raise the temperature to 70-95°C and stir, dissolve the colloidal mixture in 85-115 parts of water, add an acidic neutralizer, adjust the pH value of the system to 5.0-7.0, and cool naturally to room temperature; 6) Add 1 to 5 parts of ethylene glycol, 1 to 5 parts of methyl cellulose, 0.01 to 0.1 parts of zinc chloride, and 0.01 to 0.1 parts of boric acid, and stir to mix thoroughly.

2. The production process of the modified polyvinyl alcohol flame retardant adhesive according to claim 1, characterized in that: In step 2), stirring was continued for 12 h.

3. The production process of the modified polyvinyl alcohol flame retardant adhesive according to claim 1, characterized in that: In step 3), a polyvinyl alcohol aqueous solution with a concentration of 10 wt.% is prepared.

4. The production process of the modified polyvinyl alcohol flame retardant adhesive according to claim 1, characterized in that: In step 5), the temperature is raised to 80° C. and stirred, and the colloidal mixture is dissolved in 100 parts of water.

5. The production process of the modified polyvinyl alcohol flame retardant adhesive according to claim 1, characterized in that: In step 5), the acidic neutralizing agent is sodium hydroxide or potassium hydroxide.

6. An application of a modified polyvinyl alcohol flame retardant adhesive produced by the process according to any one of claims 1 to 5, characterized in that: The method is applied to the processing of wood products, such as floors and furniture.

7. The use of the modified polyvinyl alcohol flame retardant adhesive according to claim 6, characterized in that: It is applied to the preparation of flame-retardant solid wood composite flooring, that is, the modified polyvinyl alcohol flame-retardant adhesive is coated on the surface of the surface board and the back board, the surface board, core layer and back board are criss-crossed and assembled, and then cold-pressed, hot-pressed, cured, sliced, sanded, grooved, and coated with flame-retardant paint, and then dried and graded and packaged.

8. The use of the modified polyvinyl alcohol flame retardant adhesive according to claim 7, characterized in that: The coating amount of modified polyvinyl alcohol flame retardant adhesive on the surface panel is 150-180g / ㎡; the coating amount of modified polyvinyl alcohol flame retardant adhesive on the back panel is 160-190g / ㎡.

9. The use of the modified polyvinyl alcohol flame retardant adhesive according to claim 7, characterized in that: Cold pressing time 20min, pressure 10~11kg / cm 2 .

10. The use of the modified polyvinyl alcohol flame retardant adhesive according to claim 7, characterized in that: Hot pressing time is 360s, temperature is 93~98℃.

Citation Information

Patent Citations

  • Formaldehyde-free flame-retardant solid wood composite floor and modified lignin-based flame-retardant adhesive

    CN116038849A

  • Flame-retardant laminated solid wood composite floor and preparation method thereof

    CN117926993A